Structural regularities of welded seam between Ti-TiB and vanadium with 12X18H10T interlayer by using electron beam welding - P. Loboda; C. Zvorykin; V. Zvorykin; Vrzhyzhevskyi E. Vrzhyzhevskyi E.; T. Taranova; V. Kostin (Mechanics and Advanced Technologies)
Possibilities of obtaining and using an intermediate layer for joining of Ti-TiB and austenitic steel 12X18H10T (analog of AISI 321; 1.4541; X10CrNiTi18-10) were studied. An alloyed interlayer with TiB reinforcing fibers and the main alloying elements of 12X18H10T steel was formed on the surface of the Ti-TiB sample. Such interlayer was formed during electron beam welding of Ti-TiB with vanadium using foil made of 12X18H10T steel. The microstructure of the interlayer consists of a metal matrix reinforced with microfibers. It’s composition corresponds to vanadium-alloyed titanium boride. In comparison to the initial Ti-TiB alloy, significant grinding of reinforcing boride microfibers in the interlayer microstructure was observed. Besides, the phase formations close to Ti2B in zone of primary titanium borides decomposition in the interlayer, initiated by electron beam were determined. As a result, application of Ti (63-68 at.%) and V (18-25 at.%) based interlayer with alloying additives (Fe, Cr, Ni, B, C) has great potential for utilization in electron-beam welding of 12Х18Н10Т steel with Ti-TiB alloy.